팔라듐 복합막을 이용한 잠수함 연료전지용 메탄올 개질가스 수소정제에 관한 연구 - 이은한(Eun-Han Lee); 김태우(Tae-Woo Kim); 변세기(Se-Gi Byun); 서두원(Doo-Won Seo); 황효정(Hyo-Jung Hwang); 김한성(Hansung Kim); 이신근(Shin-Kun Ryi) (Clean Technology, 28(1), 2022)
This study examined the use of palladium (Pd)-composite membranes for hydrogen purification from methanol reforming gas for the operation of air independent propulsion (AIP) submarines. Since submarines utilize low-temperature polymer electrolyte fuel cells (LT-PEMFC) and one of the requirements of these fuel cells is high-purity (99.999%) hydrogen, a dense membrane without pinholes is an essential requirement for a Pd-composite membrane. A Pd-composite membrane for methanol reformed gas purification was made by electroless plating an Inconel 600 support coated with yttrium stabilized zirconia (YSZ) as a diffusion barrier layer using the blowing coating method (BCM). The membrane was tubular with a length of 450 mm and a diameter of 12.7 mm (surface area of 175 cm2). Hydrogen purification tests were carried out with simulated methanol reformed gas containing approximately 67% hydrogen at 400 ℃, a hydrogen permeation pressure of 2.5 bar, which is that of LT-PEMFCs used for AIP submarines, and a feed pressure of 25 bar. The purification tests showed that the approximately 67% hydrogen of the methanol reformed gas could be purified up to 99.999% with 80.1% hydrogen recovery when the reformed gas feeding rate was 0.53 Nm3 h-1. These results indicated that the hydrogen purification capacity of the membrane was 0.29 Nm3 h-1. After the high-pressure purification tests, the Pd-composite membrane was disassembled from the module and the surface condition and thickness were analyzed. Membrane analysis showed no membrane damage and the palladium thickness was 11 to 12 ㎛ meaning that the plating efficiency was approximately 92%. From the purification tests and the membrane analysis, we could conclude that the developed Pd-composite membrane can be used as a hydrogen purifier for the fuel supply system of AIP submarines. 본 연구는 팔라듐계 복합막을 사용하여 메탄올개질을 통한 on-site 제조 수소를 air independent propulsion (AIP)용 잠수함 운용에 활용하기 위한 수소 정제에 관한 것이다. 잠수함용 연료전지는 저온형 고분자전해질연료전지(low-temperature proton exchange membrane fuel cell, LT-PEMFC) 이며, 잠수함 운용 특성상 99.999% 고순도 수소가 필요하기 때문에 팔라듐 복합막은 핀홀(pinhole)이 없는 치밀막이 필수요구사항이다. 메탄올 개질가스 정제에 사용한 분리막은 blowing coating method(BCM) 법으로 yttrium stabilized zirconia (YSZ) 확산방지층을 코팅한 길이 450 mm, 직경 12.7 mm인 (표면적 175 cm2) 인코넬 600 지지체에 무전해도금법으로 팔라듐을 코팅하여 제조하였다. 제조된 팔라듐계 복합막을 사용하여 수소농도가 ~ 67%인 메탄올개질 혼합가스를 공급하면서 운전온도 400 ℃, 잠수함 사용에 적합하도록 LT-PEMFC에 수소를 공급하기 위한 수소투과측 압력 2.5 bar, 그리고 분리막측 공급압력 25 bar에서 수소정제실험을 진행하였다. 메탄올개질 혼합가스 정제실험 결과 분리막 1개당 0.53 Nm3 h-1까지 메탄올 개질가스 정제가 가능하였는데 수소농도는 99.999% 이상 정제가 가능하였고, 이때 수소회수율은 80.1%에 달하였다. 이는 분리막 1개 당 메탄올 개질 가스로부터 99.999% 이상 수소를 생산할 수 있는 용량이 0.29 Nm3 h-1임을 의미한다. 고압실험 후 분리막은 모듈에서 해체하여 표면상태, 두께 등을 분석하였는데 고압운전에도 분리막 손상은 없었고, 두께는 11-12 ㎛임을 확인하였다. 측정한 두께로 도금효율이 약 92%에 달하는 수치임을 확인하였다. 개발한 팔라듐계 복합막을 이용한 수소정제실험 및 분리막 분석을 통하여 고압운전이 필요한 AIP용 잠수함 운용에 필요한 연료공급장치에 수소정제기로 활용 가능함을 알 수 있었다.